Phoenix Man, An Example of Stigmatization Phenomenon in the China Social Media - Chengmeng Zhang (International Journal of Engineering and Management Research, 2019)
With the rapid transformation and development of contemporary Chinese network society, the phenomenon of stigmatization is becoming more and more common in social media communication. The theory about the social stratum and the mobility of society could give us a good theoretical explanation, it could help us understand why a group is stigmatized and excluded. The purpose of this article was to find out the formation mechanism of stigmatization with Phoenix man through literature review and qualitative analysis, linked this phenomenon to social mobility and anxiety of middle-class in China, and finally point out the existing deep-seated social inequality problems and hazards in China. Through the network search engine "Baidu" and literature review, get the network search index and some other social media information about Phoenix Man, found the process (initial, development and final) of stigmatization phenomenon of Phoenix Man, and made reasonable analysis. By compared Phoenix Man with the two groups, Zhuanjia and Gongzhi, it easily to find that Phoenix Man have always been highly concerned in Chinese social media. Finally, this study found that the stigmatization was originated from the anxiety caused by differences in cultural, customs and habits between middle-class and the lower-class. The stigmatization made the people who came from lower class groups been marginalized, also damaged social justice and harmony.